Global research progress on rural settlement spatial patterns from 2000–2024: a comprehensive review of hotspots, frontiers, and emerging trends - Huang, Yuhao; Xia, Jun; Chen, Yile; Hong, Jiaqi (Frontiers in Earth Science, 2024)
Rural settlements serve as the fundamental spatial unit in rural geography research and play a significant role in regional system research on human‒land relations. With the accelerated advances in urbanization, industrialization, and agricultural modernization, the flow of urban and rural development factors has greatly changed the social and economic forms of rural areas, further seriously restricting the sustainable development of rural economies and societies. The spatial patterns of rural settlements serve as tangible reflections of rural living and the evolution of settlement structures, directly influencing the sustainable development of rural areas and the construction of rural human settlements. Despite the increasing number of relevant studies, a comprehensive review of the field’s dynamic evolution, research frontiers, and future development trajectories remains incomplete. On the basis of the Web of Science core database, this study used CiteSpace 6.2 R4 and VOS Viewer 1.6 software to perform a full systematic review of the literature on rural settlement spatial morphology from 2000 to 2024. The goal was to determine the current state of the research, where researchers are most active, and what major ideas and trends can be expected in the field of rural settlement spatial patterns. The results indicate that (1) the spatial patterns of rural settlements are a popular topic, integrating different disciplines and covering various themes, with close regional cooperation and a growing number of publications. At the national level, China, the United States, and France lead in research output and influence in this field. (2) The main research hotspots in the field include rural residential areas, spatial organization, land use, driving mechanisms, and regional systems, all of which are related to rural sustainable development. (3) Future research trends will likely focus on the response of rural settlement spatial patterns to new urbanization processes and social contexts. The findings provide a comprehensive overview of the evolution of research hotspots, aiding researchers in related fields in quickly grasping the research frontiers and summaries.